2017
DOI: 10.1111/cmi.12798
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils differentially attenuate immune response toAspergillusinfection through complement receptor 3 and induction of myeloperoxidase

Abstract: Invasive aspergillosis (IA) remains a major cause of morbidity in immunocompromised hosts. This is due to the inability of the host immunity to respond appropriately to Aspergillus. An established risk factor for IA is neutropenia that is encountered by patients undergoing chemotherapy. Herein, we investigate the role of neutrophils in modulating host response to Aspergillus. We found that neutrophils had the propensity to suppress proinflammatory cytokine production but through different mechanisms for specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For example, the modulation of IL-1β production by Aspergillus is cellular contact-dependent with the involvement of complement receptor 3. Inhibition of TNF-α is cell contact-independent and mediated by secreted MPO through the TLR4 pathway [86]. Furthermore, there are two waves of neutrophils entering dLNs after immunization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the modulation of IL-1β production by Aspergillus is cellular contact-dependent with the involvement of complement receptor 3. Inhibition of TNF-α is cell contact-independent and mediated by secreted MPO through the TLR4 pathway [86]. Furthermore, there are two waves of neutrophils entering dLNs after immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are abundant in peripheral circulation, are well characterized in host defense against bacteria, and play a signi cant role in shaping adaptive immunity [30]. A recent study showed that neutrophils inhibited IL-1β and TNF-α production by CD14 + monocytes in cell-cell contact-dependent and independent manners [31]. Moreover, neutrophils have the capacity to inhibit T-cell proliferation through the expression of Mac-1 and ROS during acute in ammation [32].…”
Section: Discussionmentioning
confidence: 99%
“…A. Terreus infection often leads to superficial infections in man whereby the inhalation of spores initiates the immediate recruitment and activation of macrophages and neutrophils that overwhelms the infection [ 38 ]. However, in immunosuppressed individuals with neutropenia, or with a compromised capacity for neutrophil phagocytosis, this response is less vigorous [ 39 ].…”
Section: Discussion and Conclussionsmentioning
confidence: 99%